UPAYA MENINGKATKAN HASIL BELAJAR BOLA VOLIMELALUI PERMAINAN BOLA BATAS BAGI SISWA KELAS IV SD NEGERI GONDANG KABUPATEN BATANG TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of research is an effort to improve learning outcomes through the game of volleyball with a ball onthe boundary Elementary School fourth grade students Gondang Batang in the Academic Year 2012/2013.This research is a classroom action research was conducted in two cycles. Each cycle has four steps: Planning,Execution, Observation and Reflection. Techniques of collecting data through observation, tests and researchskills learning outcomes. Data analysis technique used in this study is a qualitative descriptive statistics.Cognitive learning outcomes silkus I obtained an average value of 73.8 with a passing grade achieved 50%. Inthe second cycle the average values obtained 81.67 with mastery learning achieved 88.89%. Affective learningoutcomes silkus I obtained an average value of 70.3 with a passing grade is achieved 55.56%. In the secondcycle the average values obtained 87.55 with mastery learning achieved 94.44%. Psychomotor learningoutcomes silkus I obtained an average value of 70.3 with a passing grade achieved 50%. In the second cycle theaverage values obtained 82.83 with mastery learning achieved 83.33%. Based on the results of the second cyclecan be concluded that the boundary through the game ball to improve learning outcomes in learning volleyball.Based on the results of this study concluded that through the game of limit can improve student learningoutcomes in the game of volleyball for students of Class IV Elementary School District Gondang Blado Batangin the Academic Year 2012/2013.